Clinical course of non‐specific low back pain: A systematic review of prospective cohort studies set in primary care. (28th May 2012) - Itz, C.J.; Geurts, J.W.; van, M.; Nelemans, P.
Abstract Background and objective Non‐specific low back pain is a relatively common and recurrent condition for which at present there is no effective cure. In current guidelines, the prognosis of acute non‐specific back pain is assumed to be favourable, but this assumption is mainly based on return to function. This systematic review investigates the clinical course of pain in patients with non‐specific acute low back pain who seek treatment in primary care. Databases and data treatment Included were prospective studies, with follow‐up of at least 12 months, that studied the prognosis of patients with low back pain for less than 3 months of duration in primary care settings. Proportions of patients still reporting pain during follow‐up were pooled using a random‐effects model. Subgroup analyses were used to identify sources of variation between the results of individual studies. Results A total of 11 studies were eligible for evaluation. In the first 3 months, recovery is observed in 33% of patients, but 1 year after onset, 65% still report pain. Subgroup analysis reveals that the pooled proportion of patients still reporting pain after 1 year was 71% at 12 months for studies that considered total absence of pain as a criterion for recovery versus 57% for studies that used a less stringent definition. The pooled proportion for Australian studies was 41% versus 69% for European or US studies. Conclusions The findings of this review indicate that the assumption that spontaneous recovery occurs in a large majority of patients is not justified. There should be more focus on intensive follow‐up of patients who have not recovered within the first 3 months.